Correction of fetal umbilical vein flow imbalance following laser surgery for twin–twin transfusion syndrome. (1st December 2022) - Saab, R. H.; DeVore, G. R.; Monson, M.; Masri, J.; Korst, L. M.; Chmait, R. H.
ABSTRACT: Objectives: Twin–twin transfusion syndrome (TTTS) is characterized by unequal hemodynamics between the twins. We aimed to assess preoperatively the difference in umbilical vein flow (UVF) between the recipient and donor monochorionic diamniotic twins and evaluate the change in UVF following laser surgery in both twins. Methods: This was a retrospective cohort study of differences in UVF that occurred following laser surgical treatment of TTTS. Sonographic assessment of the umbilical vein before and 24 h after fetoscopic laser surgery for TTTS was performed. Umbilical vein diameter and time‐averaged maximum velocity were measured, and UVF per kg (UVF/kg) was converted into a Z ‐score by a calculator created using gestational age as an independent variable. Z ‐score values were converted into centiles, which were evaluated statistically. Median differences in UVF/kg centile values were adjusted for TTTS stage and presence of arterioarterial anastomoses. Results: The study population consisted of 363 TTTS patients. The adjusted preoperative median difference in UVF/kg centile between the recipient vs donor twin was 17.9% (−17.1% to 57.6%), P  < 0.0001. The adjusted median difference in UVF/kg centile between the postoperative vs preoperative period among recipients was 2.2% (−10.8% to 13.8%), P  < 0.0001, while the adjusted median difference among donors was 27.3% (8.2%–34.6%), P  < 0.0001. Conclusion: The preoperative difference in UVF between the recipient and donor twins confirms the pathophysiology of TTTS. Postoperatively, the substantial increase in UVF of the donor twin and the relatively small increase in UVF of the recipient twin confirm that ablation of the vascular communications resulted in rapid improvement in perfusion of the donor twin. © 2022 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology.